Imagination, Creativity and Fantasy in Lev S. Vygotski: An approximation to his sociocultural approach - Alessandroni, Nicolás (2017)
This article has two aims. First, to expose briefly some characteristics of the key conceptual categories of sociocultural approaches, both in its Vygotskian (Historical-Cultural Theory) and post-Vygotskian interpretations. This will lay the conceptual foundations needed to address the second aim, that is, to analyse the text Imagination and Creativity in the Adolescent [Pedologija podrostka (Pedagogy of the Adolescent), 1931] by Lev S. Vygotski. This text makes up a useful case to explain the author’s sociocultural approach about creativity and its relationship with other psychological functions within the sociogenetic development of subjects, as well as its power of creation of consciousness and auto-regulatory control.